In vitro antimicrobial effect of Gentamicin-N.sativa fusion emulsion against biofilm producing strain S.aureus, P.aeruginosa and S.epidermidis - Yaacob, Khairul Ikhwan; Yusof, Fatin Athirah; Mohd Yusof, Nazri; Mohamed, Farahidah; Mohd Shafri, Mohd Affendi (2014)

(untitled)
Bacterial resistance, arising from biofilm production is the most common problem facing in osteomyelitis, especially when implant is involved. Here, we aim to find a solution for this problem by testing the new fusion of Gentamicin Sulfate and Nigella sativa oil in emulsion form against biofilm producing strain microorganism. A fusion of Gentamicin-N.sativa formulated in the form of water-in-oil (w/o) and oil-in-water (o/w) emulsion. The final concentration of N.sativa oil varied from 32.5% (v/v) to 46.6% (v/v) and Gentamicin concentration was constant with 1% (w/v). After measurement of emulsion parameters (organoleptic characteristics, pH, particle size, different storage temperature) finished and passed stability and stress testing, they were subjected for Disc Diffusion Test to screen the effect against bacteria. Three species of bacteria used which were S.aureus (ATCC 29213), P.aeruginosa (ATCC 70888), and S.epidermidis (isolated from osteomyelitic patient). Biofilm formation abilities was confirmed and assessed using the Microtitre Plate Method. S.epidermidis used in this study also has been identified as Gentamicin resistant. Briefly, 20µl of each emulsion, N.sativa oil alone, and 1% gentamicin loaded in blank discs (Oxoid) and placed on Mueller Hinton Agar media that has been spread with bacteria previously. Later, all plates incubated at 37°C for 18 to 24 hours ±30 minutes. Mean diameter of the zone of inhibition measured after incubation and analyzed using one way ANOVA for comparison between emulsions, 1% Gentamicin, and N.sativa oil alone. All four emulsions tested against S.aureus showed slightly higher zone of inhibition than 1% Gentamicin but only emulsion D has a p value<0.05 and the other emulsions have p value>0.05, while on the P.aeruginosa the zone inhibition of emulsions showed slightly lower than Gentamicin with p value>0.05. For S.epidermidis, all emulsions showed significantly higher zone inhibition than Gentamicin with p value<0.05. All N.sativa alone (with same percentage concentrations in each emulsion) produced an effect against S.aureus and S.epidermidis except for P.aeruginosa. However the effect was much lower compared to all emulsions and Gentamicin Sulfate. Even though the effect against S.aureus and P.aeruginosa were not significantly different compared to Gentamicin alone, surprisingly it is significantly effective against gentamicin resistant S.epidermidis